Efektivitas Iklan Dan Citra Merek Terhadap Keputusan Pembelian Online Pada Konsumen Shopee - Al Hilal Faros Agusta. D; Ihwan Susila (Cattleya Darmaya Fortuna, 2024)
This study aims to analyze the effectiveness of advertising and brand image on online purchasing decisions in shopee consumers. To determine the effectiveness of advertising and brand image on shopee consumers.This study also analyzes whether advertising and brand image have an effect on online purchasing decisions on shopee consumers. The population in this study were people who used the shopee application and the sample studied was 165 respondents (sample). The data was examined using smartPLS.The results of hypothesis testing that have been carried out show that: 1) Advertising has a positive effect on purchasing decisions. 2) Advertising has a positive effect on brand image. 3) Brand image is positive for purchasing decisions.